The Role of Fund Managers in Diversifying Endowment Investment Portfolios of Malaysian Public Universities - Nurul Adilah Hasbullah; Asmak Ab Rahman (Asian Academy of Management Journal, 2023)
Endowment is one of the most important sources of income globally for higher education institutions, and it should be invested for permanent use. Unfortunately, such funds are not optimally managed in Malaysia’s public universities. Therefore, this study was conducted to find ways to manage funds effectively among universities with the highest recorded collection of endowment funds. The participating universities in the study were: Universiti Malaya, Universiti Kebangsaan Malaysia, and Universiti Teknologi Malaysia. Interviews were conducted with representatives from their financial divisions. This study found that endowment funds in Malaysian public universities can be better invested with the appointment of dedicated fund managers. Their role is to assess the assets in which to invest with their expert knowledge to enhance the investment portfolio of endowment funds.